Sex Differences in Differential Fear Conditioning During the Acquisition and Consolidation of Learned Safety - (:unkn) unknown (My University, 2017)
The ability to distinguish between threatening and non-threatening situations requires careful regulation of behavioral and physiological responses to stress and fear. Deficits in fear regulation are maladaptive and can lead to the development of anxiety disorders such as PTSD. Women are nearly twice as likely to develop PTSD as are men and laboratory animal studies have shown facilitated fear acquisition, resistance to fear extinction, deficits in extinction retention and impaired discrimination between danger and safety cues in females. Taken together this suggests a propensity for reduced inhibitory control over fear responding in females. Here we investigate the mechanisms underlying fear discrimination deficits in females using an auditory differential fear conditioning procedure. Our results suggest that fear discrimination depends on successful memory consolidation of the excitatory fear signal as well as the inhibitory safety signal. Female but not male rats showed indiscriminate fear responding to both the fear and safety cue and this may be due to impairments in learned safety by female rats. Moreover, CS- retrieval in males but not females was sufficient to destabilize synapses encoding the CS+ memory trace. Together these data suggest that sex differences in the discrimination of fear and safety may be the result of deficits in the consolidation of learned safety in females and further supports the idea that deficits in fear regulation underlie the increased risk of PTSD in female.
Keywords: Ampa; Amygdala; Estrous; Fear Conditioning; Safety; Sex Difference